Polymorphisms of haemostasis genes as risk factors for preterm delivery - Härtel, Christoph; von Otte, Sören; Koch, Julia; Ahrens, Peter; Kattner, Evelyn; Segerer, Hugo; Möller, Jens; Diedrich, Klaus; Göpel, Wolfgang (Thrombosis and Haemostasis, 2005)
Clinical trials evaluating the potential benefit of anticoagulant treatment in pregnant women with inherited thrombophilia are based on the observation that a genetic predisposition to thrombosis is associated with frequent abortions and preterm birth. It was the aim of our study to delineate the impact of genetic polymorphisms with prothrombotic and antithrombotic effects on the occurrence of preterm birth in a large cohort of very-low-birth-weight (VLBW)-infants and their mothers. We examined the factor V Leiden and the prothrombin G20210A mutation, the factor VII 121del/ins and the factor XIII Val34Leu polymorphism in preterm very-low-birth-weight (VLBW, n=593) and term-born-infants (n=278) and their mothers (n=785).The primary outcome was preterm vs. term birth. From all polymorphisms tested, the maternal factor VII-121del/ins polymorphism (26.2 vs. 17.6 %; p=0.009) and the infant’s factor VII-121del/ins polymorphism (29.0 vs. 20.0 %; p=0.009) were more frequent in singletonVLBW and their mothers compared to term infants and their mothers. Furthermore, the frequency of the factor XIII-Val34Leu polymorphism was significantly lower in singleton VLBW than in term infant controls (5.1 vs. 9.6%, p=0.025). In a multivariate regression analysis, previous preterm delivery (OR=3.8, 95% CI: 1.7–8.4), the maternal carrier status of the factor-VII-121del/ins polymorphism (OR=1.7, 95% CI: 1.12–2.5, p=0.007) and the lower frequency of infant’s factor-XIII-Val34Leu polymorphism (OR=0.53; 95% CI: 0.29–0.96; p=0.038) were found to be independently associated with preterm delivery. InVLBW mothers with pathological CTG as cause of preterm delivery, the frequency of factor V Leiden mutation was significantly increased compared to VLBW mothers without pathological CTG (14.1 vs. 6.1%, p=0.01).The investigated haemostasis gene polymorphisms have a much lower impact on subsequent preterm delivery than known risk factors such as previous preterm birth. The reported association of the factor-VII-121del/ins polymorphism on preterm delivery and its clinical relevance needs to be further elucidated.
Keywords: Preterm delivery; coagulation system; factor VII/ factor XIII